PENGARUH PARTISIPASI PEMAKAI DAN PERSEPSI KEBERMANFAATAN TERHADAP KEPUASAN PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH - . Latifah; Afrizal; Wirmie Eka P (Jurnal Akuntansi & Keuangan Unja, 2016)
This study is entitled the effect of user participation and perceived usefulness to user satisfaction in the development of regional financial accounting information systems. The purpose of this study is (1) to determine the effect of User Participation and Perception of Utilization simultaneously on the User Satisfaction of the Regional Financial Accounting Information System. (2) to determine the effect of User Participation and Perception of Partial Benefit on the Satisfaction of Users of the Regional Financial Accounting Information System This research takes the form of a survey by distributing questionnaires directly to the sample. Data analysis techniques used multiple regression analysis. The results of this study indicate that (1) User Participation and Perception of Benefit simultaneously influence the Satisfaction of Users of Regional Financial Accounting Information Systems, (2) User Participation and Benefit Perception have a partial effect on the User Satisfaction of Regional Financial Accounting Information System.